Anti-erosion and anti-permeation yttrium oxide refractory material as well as preparation method and application thereof

By adding sintering aids to the yttrium oxide refractory material and adopting ball milling and solid phase sintering processes, the sintering temperature is reduced and the density and corrosion resistance of the material are improved, and the problems of high sintering temperature and second phase precipitation of yttrium oxide refractory material in the prior art are solved, thereby achieving efficient alloy melt diffusion and contact area reduction effects.

CN119661224AActive Publication Date: 2025-03-21NANJING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411892881.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The sintering temperature of existing yttrium oxide refractory materials is high, resulting in high manufacturing costs and strict equipment requirements. It is easy to precipitate the second phase during low-temperature sintering, affecting the density and chemical stability of the material.

Method used

By adding sintering additives such as TiO2, SrO or CaO, the sintering temperature of yttrium oxide is reduced, and through ball milling and solid-phase sintering processes, the additives are fully dissolved in yttrium oxide, thereby improving the density of the material and erosion-resistant penetration ability.

Benefits of technology

A high density, second phase precipitation of yttrium oxide refractory material is prepared at a lower sintering temperature, which significantly reduces the diffusion depth of the alloy melt in the refractory material and the contact area between the melt and the refractory material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661224A_ABST
    Figure CN119661224A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-erosion and anti-permeation yttrium oxide refractory material as well as a preparation method and application thereof. According to the method, a small amount of sintering aid powder is doped into YO powder to reduce the sintering temperature, and meanwhile, the granularity of the powder, cold isostatic pressing parameters and a sintering process are regulated and controlled to prepare the YO refractory material which is high in density and large in grain size and does not generate a second phase. The method disclosed by the invention is suitable for preparing the powder for the Y2O3 crucible and the cold isostatic pressing formed Y2O3 crucible, and the erosion and infiltration resistance of the crucible to the titanium-aluminum alloy melt can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of refractory materials, and in particular relates to an anti-corrosion and penetration yttria refractory material, a preparation method and application thereof. Background Art

[0002] Oxide crucibles are used instead of water-cooled copper crucibles for titanium-aluminum alloy smelting, which can increase the superheat temperature of the melt and reduce energy consumption. Compared with refractory materials such as alumina, magnesia, and zirconia, yttrium oxide (Y2O3) has high thermodynamic stability and high chemical inertness to titanium-aluminum alloys. The use of Y2O3 crucibles can reduce oxygen contamination of ingots. In addition to thermodynamic factors, the density of Y2O3 refractory materials will affect the degree of interfacial reaction between the alloy melt and the refractory materials. When the grains of Y2O3 refractory materials are fine and the structure is loose and porous, the invasion of the melt will lead to the melting of the grains, thereby increasing the number of inclusions inside the alloy and increasing the oxygen content. Increasing the density of refractory materials is conducive to inhibiting the diffusion of the melt into the interior of the refractory material, reducing the contact area between the melt and the oxide, and reducing the interaction.

[0003] However, the melting point of Y2O3 is greater than 2400°C, and the sintering temperature required to achieve a higher density is relatively high (not less than 1700°C), which increases the manufacturing cost and the performance requirements for production equipment. Chinese patent application number CN202210099193.5 discloses a method and crucible for preparing yttria refractory products by gel injection molding. The crucible is prepared using pure yttria powder. The sintering temperature required for the green body is 1750°C to 1850°C, which has high requirements for equipment. In order to reduce the sintering temperature of Y2O3 refractory materials and improve the density, a method of adding a second phase can be used (Li H, Liu Y, Yang J, et al. Preparation and application evaluation of La2O3-doped Y2O3 crucible materials for melting TiAlalloys. Ceram Int. 2022; 48: 15762-15769.). The patented technology of "A method for sintering yttria ceramic crucible at low temperature" (202110388155.7) uses magnesium oxide powder and titanium oxide powder as sintering aids to reduce the sintering temperature of yttria ceramics, but there are a large number of second phases in the microstructure. More second phases with lower thermodynamic stability will intensify the interaction between the material and the alloy. Therefore, it is necessary to select the appropriate type of elements and control the amount of element addition. Summary of the invention

[0004] The purpose of the present invention is to provide a method for reducing the sintering temperature of Y2O3 and improving the density of Y2O3 refractory materials by adding a sintering aid. The preparation method is simple and is suitable for preparing Y2O3 crucible powder and cold isostatic pressing Y2O3 crucible, which can effectively improve the corrosion and penetration resistance of the crucible.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a corrosion-resistant and permeable yttria refractory material, comprising the following steps:

[0007] (1) Powder pretreatment: Y2O3 powder and sintering aid powder are mixed in proportion, an equal amount of anhydrous ethanol is added to the obtained mixture for ball milling, followed by drying and solid phase sintering to obtain Y2O3 powder with doped element solid solution and ball milling again, wherein the sintering aid powder is one of TiO2, SrO and CaO;

[0008] (2) Green blank forming: adding a PVA aqueous solution to the powder obtained after ball milling, mixing evenly and then granulating; the powder obtained by granulation is dry pressed into a disc at 4-6 MPa, and then the disc is heated to 400-800°C for 3-5 hours to decompose the PVA; finally, the disc is cold isostatically pressed at 180-200 MPa;

[0009] (3) Sintering: The disc blank is placed in a muffle furnace for high-temperature sintering to obtain the Y2O3 refractory material.

[0010] Furthermore, the purity of the Y2O3 and sintering aid powders is 99.99%, and the powder particle size range is 1 to 3 μm.

[0011] Furthermore, the molar ratio of Y2O3 to sintering aid powder is 100:1 to 5, preferably 100:1.

[0012] Furthermore, in step (1), the ball milling time is 12 to 24 hours, and the rotation speed is 190 to 220 r / min.

[0013] Furthermore, in step (1), solid phase sintering refers to heating the temperature in a muffle furnace to 1300-1350° C. at a heating rate of 3-5° C. / min, keeping the temperature for 10-12 hours, and then cooling with the furnace.

[0014] Furthermore, in step (2), the amount of PVA aqueous solution used is 6-10% of the mass of the powder, and the concentration of the PVA aqueous solution is 5-10wt.%.

[0015] Furthermore, in step (2), the powder particle size obtained by granulation is 120 to 200 meshes.

[0016] Furthermore, in step (2), the holding time of the cold isostatic pressing is 1000 to 1800 seconds.

[0017] Furthermore, in step (3), the sintering temperature is 1650°C to 1700°C, the holding time is 8 to 16 hours, and the heating rate is 2 to 5°C / min.

[0018] In a second aspect, the present invention provides a corrosion-resistant and permeable yttria refractory material prepared by the method described in the first aspect.

[0019] In a third aspect, the present invention provides a crucible material, which is a corrosion-resistant and permeable yttria refractory material prepared by the method described in the first aspect.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0021] The present invention selects raw materials with a purity of 99.99% for preparation to avoid the generation of the second phase caused by excessive impurities. A small amount of sintering aid is evenly mixed with Y2O3 powder by ball milling, and the sintering aid is fully dissolved in Y2O3 by solid phase sintering. At the same time, a green billet with a high volume density is obtained by controlling the particle size of the powder and the cold isostatic pressing parameters. The green billet can form a refractory material with high density, large grains and no second phase precipitation at a relatively low sintering temperature. The method of the present invention can significantly reduce the diffusion depth of alloy melt (such as titanium aluminum alloy) in the refractory material and reduce the contact area between the melt and the refractory material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are SEM images of cross sections of refractory materials obtained from examples and comparative examples of the present invention, (a): Example 1, (b): Example 2, (c): Example 3, (d): Comparative Example 1.

[0023] Figure 2 The interface microstructure (a) and element distribution diagram (b) of the refractory material obtained in Example 1 after the reaction with the TiAl alloy melt.

[0024] Figure 3 The interface microstructure (a) and element distribution diagram (b) of the refractory material obtained in Example 2 after the reaction with the TiAl alloy melt.

[0025] Figure 4 The interface microstructure (a) and element distribution diagram (b) of the refractory material obtained in Example 3 after the reaction with the TiAl alloy melt.

[0026] Figure 5 The interface microstructure (a) and element distribution diagram (b) of the refractory material obtained in Example 1 after the reaction with the TiAl alloy melt are shown. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below by specific examples. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It is necessary to point out here that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art in this field according to the above invention content still belong to the scope of protection of the present invention.

[0028] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0030] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0031] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0032] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.

[0033] The embodiments of the present application provide a carborane sulfide compound and a preparation method thereof. The following are described in detail. It should be noted that the description order of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 5, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0034] Example 1

[0035] (1) Powder pretreatment: Y2O3 powder and TiO2 were mixed at a molar ratio of 100:1, and anhydrous ethanol of the same mass as the powder was added to the obtained mixture for ball milling for 24 hours at a speed of 220 r / min. Then the mixture was dried and solid-phase sintered in a high-temperature muffle furnace, and the temperature was raised to 1300°C at a rate of 5°C / min and kept at this temperature for 10 hours. After sintering, Y2O3 powder with Ti element solid solution was obtained, and it was ball milled again.

[0036] (2) Green blank molding: 10 wt% PVA aqueous solution (with a concentration of 10 wt.%) was added to the powder, mixed evenly and then granulated; the powder obtained by granulation was dry pressed into discs at 4 MPa. The discs were then heated to 600°C for 5 hours to decompose the PVA; finally, cold isostatic pressing was performed at 200 MPa for 1800 seconds.

[0037] (3) Sintering: The green blank is sintered at a high temperature of 1700°C, kept at the sintering temperature for 8 hours, and then cooled in the furnace to obtain the yttrium oxide refractory material. The cross-sectional SEM of the yttrium oxide refractory material is as follows: Figure 1 As shown in (a), the Ti-containing Y2O3 refractory material is dense and has a cross-sectional porosity of 0.02%, as shown in Table 1.

[0038] The obtained refractory material is placed between two TiAl alloys and placed in an induction vacuum suspension furnace for reaction. The micromorphology of the interface between the refractory material and the TiAl alloy melt after the reaction is as follows: Figure 2 As shown, there is no obvious reaction layer between the refractory material and the melt, and there is no obvious Al element enrichment inside the refractory material, which indicates that the refractory material can significantly reduce the diffusion depth of titanium aluminum alloy in the refractory material and reduce the contact area between the melt and the refractory material.

[0039] Example 2

[0040] (1) Powder pretreatment: Y2O3 powder and SrO are mixed in proportion, the molar ratio of Y2O3 to SrO is 100:1, and an equal amount of anhydrous ethanol is added to the obtained mixture for ball milling. The ball milling time is 12 hours and the speed is 220r / min. Then it is dried and solid-phase sintered in a high-temperature muffle furnace, and the temperature is increased to 1300℃ at a rate of 5℃ / min and kept at this temperature for 10 hours. After sintering, Y2O3 powder with Sr element solid solution is obtained, and it is ball milled again.

[0041] (2) Green blank molding: 10 wt% PVA aqueous solution (with a concentration of 5 wt.%) was added to the powder, mixed evenly and then granulated; the powder obtained by granulation was dry pressed into discs at 4 MPa. The discs were then heated to 600°C for 5 hours to decompose the PVA; finally, cold isostatic pressing was performed at 200 MPa for 1800 seconds.

[0042] (3) Sintering: The green blank is sintered at a high temperature of 1650°C, kept at the sintering temperature for 12 hours, and then cooled in the furnace to obtain the yttrium oxide refractory material. The cross-sectional SEM image is as follows: Figure 1 As shown in (b), the Sr-containing Y2O3 refractory material is dense and has a cross-sectional porosity of 0.6%, as shown in Table 1.

[0043] The interface microstructure after reaction with TiAl alloy melt is as follows: Figure 3 As shown, there is no obvious reaction layer between the refractory and the melt, and there is no obvious Al element enrichment inside the refractory.

[0044] Example 3

[0045] (1) Powder pretreatment: Y2O3 powder and CaO were mixed in proportion, the molar ratio of Y2O3 to CaO was 100:1, and an equal amount of anhydrous ethanol was added to the obtained mixture for ball milling. The ball milling time was 18 hours and the speed was 200r / min. Then it was dried and solid-phase sintered in a high-temperature muffle furnace, and the temperature was raised to 1300℃ at a rate of 3℃ / min and kept at this temperature for 10 hours. After sintering, Y2O3 powder with CaO element solid solution was obtained, and it was ball milled again.

[0046] (2) Green blank molding: 10 wt% PVA aqueous solution (with a concentration of 8 wt.%) was added to the powder, mixed evenly and then granulated; the powder obtained by granulation was dry pressed into discs at 4 MPa. The discs were then heated to 600°C for 5 hours to decompose the PVA; finally, cold isostatic pressing was performed at 200 MPa for 1800 seconds.

[0047] (3) Sintering: The green blank is sintered at a high temperature of 1700°C, kept at the sintering temperature for 8 hours, and then cooled in the furnace to obtain the yttrium oxide refractory material. The cross-sectional SEM of the yttrium oxide refractory material is as follows: Figure 1 As shown in (c) in FIG. 1 , the CaO-containing Y2O3 refractory material is dense and has a cross-sectional porosity of 0.2%, as shown in Table 1.

[0048] The interface microstructure after reaction with TiAl alloy melt is as follows: Figure 4 As shown, there is no obvious reaction layer between the refractory and the melt, and there is no obvious Al element enrichment inside the refractory.

[0049] Comparative Example 1

[0050] The other processes are the same as those in Example 1, without doping sintering aids, to obtain yttrium oxide refractory material, the cross-sectional SEM of which is as follows Figure 1 As shown in (d), after sintering, the grain size is smaller and the porosity is higher, and the cross-sectional porosity is 8.9%, as shown in the table.

[0051] The microstructure of the reaction interface between it and TiAl alloy is as follows: Figure 5 As shown, there are obvious pores on the ceramic sheet side, and the interface between the alloy and the ceramic is clear. By observing the surface scan, it is found that there is Al element infiltration in the crucible, which means that the refractory material has poor resistance to melt erosion and penetration.

[0052] Table 1

[0053] Example 1 Example 2 Example 3 Comparative Example 1 Open porosity / % 0.02 0.6 0.2 8.9

[0054] The above is a detailed introduction to the preparation method of a carborane sulfide compound provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of ​​the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the present application.

Claims

1. A method for preparing a corrosion-resistant and permeable yttria refractory material, characterized in that: The following steps are involved: (1) Powder pretreatment: Y2O3 powder and sintering aid powder are mixed in proportion, an equal amount of anhydrous ethanol is added to the obtained mixture for ball milling, followed by drying and solid phase sintering to obtain Y2O3 powder with doped element solid solution and ball milling again, wherein the sintering aid powder is one of TiO2, SrO and CaO; (2) Green blank forming: PVA aqueous solution is added to the powder obtained after ball milling, and the mixture is uniformly mixed and then granulated; the powder obtained by granulation is dry pressed into discs at 4-6 MPa, and then the discs are heated to 400-800℃ for 3-5 hours to decompose PVA; finally, the discs are cold isostatically pressed at 180-200 MPa; (3) Sintering: The disc blank is placed in a muffle furnace for high-temperature sintering to obtain the Y2O3 refractory material.

2. The method according to claim 1, characterized in that The purity of the Y2O3 powder and the sintering aid powder is 99.99%, and the powder particle size range is 1-3 μm.

3. The method according to claim 1, characterized in that The molar ratio of Y2O3 to sintering aid powder is 100:1~5, preferably 100:

1.

4. The method according to claim 1, characterized in that In step (1), the ball milling time is 12-24 h and the rotation speed is 190-220 r / min.

5. The method according to claim 1, characterized in that In step (1), solid phase sintering refers to heating the temperature in a muffle furnace to 1300-1350°C at a heating rate of 3-5°C / min, keeping the temperature for 10-12 hours and then cooling with the furnace.

6. The method according to claim 1, characterized in that In step (2), the amount of PVA aqueous solution used is 6-10% of the mass of the powder, and the concentration of the PVA aqueous solution is 5-10 wt.%.

7. The method according to claim 1, characterized in that In step (2), the holding time of cold isostatic pressing is 1000~1800 s.

8. The method according to claim 1, characterized in that In step (3), the sintering temperature is 1650°C~1700°C, the holding time is 8~16 h, and the heating rate is 2~5°C / min.

9. A corrosion-resistant and permeable yttria refractory material prepared by the method according to any one of claims 1 to 8.

10. A crucible material, which is a corrosion-resistant and permeable yttria refractory material prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing crucible for smelting titanium and titanium alloys

    CN101381242A

  • Preparation method of refractory material for TiAl alloy precision casting

    CN109277518A

  • Method for sintering yttrium oxide ceramic crucible at low temperature

    CN112939603A

  • Compact yttrium oxide material and preparation method thereof

    CN115894030A

  • Manufacturing Method of Porous Clay and Porous clay

    KR102611688B1

Cited By

  • MgO-Y2O3 refractory material with multi-scale core-shell structure and preparation method of MgO-Y2O3 refractory material

    CN120794577A